Pengaruh Atribusi Laba, Atribusi Ekuitas, Ukuran Perusahaan, dan Arus Kas Operasi terhadap Kualitas Laba: Studi Kasus di Perusahaan Sub Sektor Plastik dan Kemasan yang Terdaftar di BEI Periode Tahun 2020-2022 - Ivana Wilda Afosma; Marhaendra Kusuma; Rike Selviasari (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Since PSAK converges with IFRS, the content of the income statement format is not only net income, but there are other comprehensive income and profit attribution. The latest statement of financial position contains additional information, namely equity attributable to the ownership of the parent entity and non-controlling interests. The purpose of this study is to provide evidence of observation and discovery of any influence behind the quality of profit. Population as many as 15 companies sub-sector plastic and packaging. The sample was 9 companies, with 27 observational data. The results of the analysis showed that comprehensive income and equity attributable to the ownership of the parent entity and to non-controlling interests significantly positively affect the quality of profits, while equity attributable to the owners of the parent entity, the size of the company and operating cash flows significantly did not affect the quality of profits. The novelty of this study is about the attribution of profit and equity, in the form of testing the effect of profit attribution and equity attribution on the quality of profit.